First assessment of all-cause acute diarrhoea and rotavirus-confirmed cases following massive vaccination in Argentina - Degiuseppe, J I (2018)
Fil: Degiuseppe, J I. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Laboratorio de Gastroenteritis Virales; Argentina.